Transforming education reimagining learning, pedagogy and curriculum - Jefferson, Miranda; Anderson, Michael 1969- (Bloomsbury Academic, 2021)
"Working away from trends in government policy, this book takes a future-oriented re-imagining of schools with a focus on four innate human capacities: collaboration, critical reflection, communication and creativity. Miranda Jefferson and Michael Anderson draw together a diverse range of case studies from around the world, including Australia, Canada, England, Hong Kong, Singapore and the USA, to provide a reimagining of education, showing how our schools can be sustainably transformed to be places of support, challenge and joy in learning, meeting emergent needs in our workplaces and wider society. Threading case studies throughout, readers are guided to see themselves as agents of transformation, empowered to use knowledge and experience to build the reality they would like to see in their school, responding to their questions of diversity, inclusion, and community. Key ideas are summarised at the end of each chapter along with an extensive referencing and bibliography, and a supporting glossary. A companion website includes links to additional resources, expanded audio/video interviews and activities."
Keywords: Schulreform; School improvement programs / Cross-cultural studies; School improvement programs; Cross-cultural studies